Integrating e-module craft and wedding gifts course; the effect on creative thinking and attitudes student in vocational education students - Hayatunnufus, Hayatunnufus; Yanita, Merita; Dewi, Ika Parma; Sari, Adha Kurnia; Hanafi, Hafizul Fahri; Ismail, Mazeni (Universitas Negeri Padang, 2024)
Society 5.0 envisions a future that emphasizes the integration of advanced technologies with human life to foster a more human-centered, sustainable, and inclusive community. A key skill in this context is found in the craft and wedding gift course. This course not only equips students with comprehensive knowledge of crafting techniques for wedding gifts but also prepares them to engage in the rapidly expanding field of entrepreneurship. The objective of this study is to develop an e-module focused on teaching wedding gift-making skills for vocational students. This e-module will be tailored to fulfill students' needs for an interactive, engaging, and flexible learning experience. The research employs a development research (R&D) approach, aiming to enhance the quality of education by implementing the ADDIE model. The developed e-module received a very valid assessment, with 90.67% from the media validator and 90.25% from the material validator In addition, this e-module was also considered very practical by lecturers with a score of 85% and by students with a score of 92%. The decision-making criteria were if the sig value (2-tailed) <0.05, then the proposed hypothesis was accepted.